Empirical and philosophical problems with the subspecies rank. Issue 7 (10th July 2022) - Burbrink, Frank T.; Crother, Brian I.; Murray, Christopher M.; Smith, Brian Tilston; Ruane, Sara; Myers, Edward A.; Pyron, Robert Alexander
Abstract: Species‐level taxonomy derives from empirical sources (data and techniques) that assess the existence of spatiotemporal evolutionary lineages via various species "concepts." These concepts determine if observed lineages are independent given a particular methodology and ontology, which relates the metaphysical species concept to what "kind" of thing a species is in reality. Often, species concepts fail to link epistemology back to ontology. This lack of coherence is in part responsible for the persistence of the subspecies rank, which in modern usage often functions as a placeholder between the evolutionary events of divergence or collapse of incipient species. Thus, prospective events like lineages merging or diverging require information from unknowable future information. This is also conditioned on evidence that the lineage already has a detectably distinct evolutionary history. Ranking these lineages as subspecies can seem attractive given that many lineages do not exhibit intrinsic reproductive isolation. We argue that using subspecies is indefensible on philosophical and empirical grounds. Ontologically, the rank of subspecies is either identical to that of species or undefined in the context of evolutionary lineages representing spatiotemporally defined individuals. Some species concepts more inclined to consider subspecies, like the Biological Species Concept, are disconnected from evolutionary ontology and do not consider genealogy. Even if ontology is ignored, methods addressing reproductive isolation are often indirect and fail to capture the range of scenarios linking gene flow to species identity over space and time. The use of subspecies and reliance on reproductive isolation as a basis for an operational species concept can also conflict with ethical issues governing the protection of species. We provide a way forward for recognizing and naming species that links theoretical and operational species concepts regardless of the magnitude of reproductive isolation. Abstract : The use of subspecies taxonomy has a long and problematic history in systematics and recent studies using genomic data have suggested their continued use when incompletely reproductively isolated lineages are discovered. We demonstrate that where subspecies represent ontological individuals, they are actually species, and where they are not ontological individuals they do not represent taxonomic units in evolutionary biology. We demonstrate a way forward for understanding lack of reproductive isolation among lineages in a taxonomic context.